A review of co-morbidity between infectious and chronic disease in Sub Saharan Africa: TB and Diabetes Mellitus, HIV and Metabolic Syndrome, and the impact of globalization - Johnstone Lucy K; Critchley Julia A; Young Fiona; Unwin Nigel C (Globalization and Health, 2009)
Abstract Background Africa is facing a rapidly growing chronic non-communicable disease burden whilst at the same time experiencing continual high rates of infectious disease. It is well known that some infections increase the risk of certain chronic diseases and the converse. With an increasing dual burden of disease in Sub Saharan Africa the associations between diseases and our understanding of them will become of increased public health importance. Aims In this review we explore the relationships reported between tuberculosis and diabetes mellitus, human immunodeficiency virus, its treatment and metabolic risk. We aimed to address the important issues surrounding these associations within a Sub Saharan African setting and to describe the impact of globalization upon them. Findings Diabetes has been associated with a 3-fold incident risk of tuberculosis and it is hypothesised that tuberculosis may also increase the risk of developing diabetes. During co-morbid presentation of tuberculosis and diabetes both tuberculosis and diabetes outcomes are reported to worsen. Antiretroviral therapy for HIV has been associated with an increased risk of developing metabolic syndrome and HIV has been linked with an increased risk of developing both diabetes and cardiovascular disease. Globalization is clearly related to an increased risk of diabetes and cardiovascular disease. It may be exerting other negative and positive impacts upon infectious and chronic non-communicable disease associations but at present reporting upon these is sparse. Conclusion The impact of these co-morbidities in Sub Saharan Africa is likely to be large. An increasing prevalence of diabetes may hinder efforts at tuberculosis control, increasing the number of susceptible individuals in populations where tuberculosis is endemic, and making successful treatment harder. Roll out of anti-retroviral treatment coverage within Sub Saharan Africa is an essential response to the HIV epidemic however it is likely to lead to a growing number of individuals suffering adverse metabolic consequences. One of the impacts of globalization is to create environments that increase both diabetes and cardiovascular risk but further work is needed to elucidate other potential impacts. Research is also needed to develop effective approaches to reducing the frequency and health impact of the co-morbidities described here.